The digit ratio (2D: 4D) and economic preferences: no robust associations in a sample of 330 women - Parslow, Elle; Ranehill, Eva; Zethraeus, Niklas; Blomberg, liselott; von Schoultz, Bo; Hirschberg, Angelica Lindén; Johannesson, Magnus; Dreber, Anna (Journal of the Economic Science Association, 2019)
Many studies report on the association between 2D:4D, a putative marker for prenatal testosterone exposure, and economic preferences. However, most of these studies have limited sample sizes and test multiple hypotheses (without preregistration). In this study we mainly replicate the common specifications found in the literature for the association between the 2D:4D ratio and risk taking, the willingness to compete, and dictator game giving separately. In a sample of 330 women we find no robust associations between any of these economic preferences and 2D:4D. We find no evidence of a statistically significant relation for 16 of the 18 total regressions we run. The two regression specifications which are statistically significant have not previously been reported and the associations are not in the expected direction, and therefore they are unlikely to represent a real effect.
Keywords: 2D:4D; Economic preferences; Experiment; Testosterone; C91; D03